TANTANGAN PERPAJAKAN ATAS EKONOMI DIGITAL : STUDI FENOMENOLOGI DALAM MERUMUSKAN KEBIJAKAN KEBERLANJUTAN DI INDONESIA - Andrianto, Andrianto (Majalah Ekonomi, 2025)
The transformation of the digital economy has presented significant challenges to the conventional tax system, particularly in the context of law enforcement, compliance, and regulatory accuracy. This study aims to analyze the perceptions, experiences, and constraints of digital economy actors regarding the current tax system, as well as to formulate adaptive and digital-native policy directions. The research method used is a qualitative approach with a phenomenological design through in-depth interviews with key informants from various sectors such as digital MSMEs, tax authorities, and academics. Data analysis techniques are carried out using an interpretive approach through the stages of data reduction, data presentation, and thematic conclusion drawing. The findings indicate regulatory gaps, low tax awareness, limited fiscal capacity, and weak digital law enforcement. Lessons learned from other countries such as India, Australia, and Estonia highlight the importance of technology integration and collaborative approaches. This research contributes theoretically to the development of the concept of digital fiscal governance and encourages tax policy reform based on the realities of digital businesses in Indonesia. Practical implications include recommendations for more flexible regulatory design, increased tax literacy, and the development of data- and algorithm- based monitoring systems. This research opens up opportunities for further research in the areas of digital taxation, fiscal governance, and compliance behavior in the digital economy.